EKSISTENSI RUMAH TAHFIDZ PARA SAHABAT TERHADAP PEMBERANTASAN BUTA AKSARA AL-QUR’AN DI RENGAS CONDONG MUARA BULIAN - Marzani, Marzani; Yusup, M.; Mahdayeni, Mahdayeni; Maimunah, Ira (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
The existence of Rumah Tahfidz Sahabat is the existence of an institution that can influence something where it is a place or facility for children to learn and memorize the Qur’an. This research was conducted at the Tahfidz Para Companions House. As based on the initial Grand tour, the author sees that there are still many students who cannot read the Qur’an, so the teacher (ustadzah) must be able to provide learning how to read the Qur’an properly and correctly. The research objectives to be achieved in this study are: to determine the effect of the existence of Tahfidz Sahabat’s House on the Eradication of Al-Qur’an Illiteracy in Rengas Condong, Muara Bulian District. The method used by the researcher is a quantitative method. The population in this study were 50 students, 20 students for instrument testing and a sample of 30 students. This sample was obtained from 30 students using the Slovin formula. The hypothesis in this study is Ha: r > 0 or Ha: r 0. So there is a positive and significant influence between the influence of the existence of the Tahfidz House on eradicating illiteracy in the Qur’an. This study provides an illustration that there is a positive and significant influence between the influence of the independent variable (the existence of the Tahfidz House) on the dependent variable (eradicating illiteracy of the Qur’an) of 74.8% while the remaining 25.5% is influenced or explained by other variables that not included in this research model. Although there are still students who are less able to read the Qur’an, at least the presence of this Tahfidz House can help in eradicating illiteracy of the Qur’an and can increase the motivation of students and the surrounding environment. This is evidenced by the completeness of student learning outcomes while at Tahfidz’s house